PENERAPAN KOMBINASI TERAPI BIRTHBALL DAN TEKNIK RELAKSASI NAFAS DALAM TERHADAP NYERI PERSALINAN - Marsela, Yenny; Mona, Silvia (Universitas Batam, 2024)
The treatment of non-pharmacological pain management is intended to lessen pain, particularly during the first stage of labor, pain management is more effective than pharmacological methods because it is cheap, simple effective, and without adverse effects. In the early stages, it is important to provide maternal care, which includes teaching relaxing techniques such as breathing and Birth ball therapy. The purpose of this study is to determine the efficacy of birth ball and breathing exercises. This research methodology uses a case study approach and is a form of descriptive research. In order to reduce labor pain during the active phase I of labor, one mother in the sample used deep breathing exercises and a birth ball. Through the use of a numerical rating scale (NRS) on an observation sheet, the pain level was measured. When birth ball therapy and Deep Breath Relaxation Technique are combined, laboring mothers experience a reduction in pain. During the first half hour, the results show a decrease in pain level at pain score 6 (moderate heavy), and after the second half, the results show a decrease in pain level at pain score 4 (moderate mild). In summary During the active phase I of labor, the combination of birth ball and Deep Breath Relaxation Technique effectively reduces labor pain